(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the efficacy of Solifenacin 5mg daily compared to placebo in patients with Irritative LUTS secondary to DJ stent in situ assessed by storage IPSS. Study Design: Randomized Controlled study Place and Duration of Study: This study was conducted at the Urology Unit, Benazir Bhutto Shaheed Teaching Hospital, Abbottabad from Nov 2019 May-2020. Materials and Methods: Sample size is 76 in each group, using WHO software for sample size determination in healthy studies, applying the formula of hypothesis test, for two population proportions (one- sided) with the following assumption:9 Significance level = 5% Statistical power = 80% Proportion of patients with LUTS associated with unilateral double-J stent (DJ Stent) Stenting (Group A- Mean Irritative IPSS pre and post Solifenacin treatment 7.38 vs 2.75) = 31% Proportion of patients with Lower Urinary Tract Symptoms (LUTS) associated with unilateral DJ stenting (Group B- Mean Irritative International Prostate Symptom Score (IPSS) pre and post Placebo treatment 6.38 vs 5.13) = 8% Sampling technique: Consecutive non probability sampling. Results: There was a 30.8% mean improvement of storage IPSS compared to placebo, 9.97%. This difference in efficacy between Solifenacin vs placebo was also found statistically significant (p=0.000). Conclusion: Solifenacin 5mg daily significantly improved the storage symptoms compared with placebo, in men with moderate to severe lower urinary tract symptoms due to A double-J stent (DJ Stent) stent placed in situ.